TEACHING PRACTICE IN MULTI-GRADE CLASSES IN THE FIELD: A PROPOSAL FOR A TEACHING MODEL - Aparecida da Silva Cruz, Vanessa; Souza Silva, Penha (Revista Gênero e Interdisciplinaridade, 2024)
Considering the heterogeneous context of the multiserial classes in the field, we conducted a survey using an online questionnaire with thirty public school teachers who work in these classes, from five different municipalities in Minas Gerais. The data collected pointed to the organization of teaching time as the main difficulty faced by teachers in the multi-grade classes. Other difficulties were presented, such as, for example, a certain inability with the teaching of Sciences, which, for the research subjects, is a consequence of an inefficient initial training. Based on the results of this research, we developed a Teaching Model in order to support teaching practice in the search for strategies that promote the interaction of students at different levels, using heterogeneity in favor of the teaching and learning process. Ten teachers developed the Teaching Model in their classes, and after joint analysis, they assessed that the use of activities enhanced the interaction between students from different grades gathered in the same room and contributed to a reorganization of teaching time by the teacher. Otherwise, the research subjects indicated that the use of the Teaching Model is a strategy to be used in specific moments and not daily throughout the school period.